Determinants of IPO's underpricing: A systematic review - Carlos Henrique Firmino de Oliveira; Claudia Lebre Rodrigues; Michele Nascimento Jucá (Contemporary Economics, 2023)
In an Initial Public Offering (IPO) process, it is expected that there will be different share price valuations by professionals, due to market flaws, meaning information asymmetry among investors. For stockholders - who previously formed the corporate structure of the company - an IPO opens up possibilities of immediate gains, as they can purchase at prices lower than established by the structuring agent. On the other hand, underpricing is an indirect cost for the company, as, part of the offer is not collected. Identifying these determinants thus becomes relevant, as this information may be essential for defining the most appropriate share price. Consequently, the purpose of this study is to perform a bibliometric analysis (including the Zipf, Bradford and Lotka Laws), followed by a systematic review of papers analyzing this theme. This analysis uses the VOSviewer and Biblioshiny software packages. As a result, informational asymmetry is confirmed as the main theory clarifying the underpricing event. Noteworthy among the determinants are the reputations of the underwriter and share issuer, the presence of corporate governance mechanisms, and the offering size. Among the knowledge gaps opening up opportunities for further studies on this topic are: investigation of the phenomenon in companies in Latin America or comparatively in emerging countries worldwide, use of a behavioral approach to analyze investor motivations, and the presence of institutional investors as IPO inducers.
Keywords: G12; G15; G32; 330; determinants; underpricing; IPO; bibliometric analysis; systematic review